2019
DOI: 10.34105/j.kmel.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived usefulness, confirmation and satisfaction on continuance intention in using massive open online course (MOOC)

Abstract: Massive Open Online Course (MOOC) has been playing an important role in the latest e-learning initiative and has obtained a widespread popularity in many universities. However, the low course completion rates of students have become an outstanding issue that should not be neglected. Based on the Expectation-Confirmation Model (ECM), this study examines the effects of students’ perceived usefulness, confirmation and satisfaction on MOOC continuance intention. Structural Equation Modeling (SEM) was used to valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
6
38
0
7
Order By: Relevance
“…In other words, the influence of technical support and course design on promoting continuance intention of using e-training can be strengthen if the e-training program perceived as useful by the participants [26][28].This result showed that perceived usefulness has important influence in both models i.e. direct or indirect effect model and supported by many previous studies on online learning [19][20][21][22][23][24][25] that perceived usefulness of e-learning product has significant role in influencing the willingness of users to continue using the product. Besides having a good technical support and well designed, the online platform for learning as well as training must perceived as useful by the participants in motivating them to continue using it or other platforms like it.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In other words, the influence of technical support and course design on promoting continuance intention of using e-training can be strengthen if the e-training program perceived as useful by the participants [26][28].This result showed that perceived usefulness has important influence in both models i.e. direct or indirect effect model and supported by many previous studies on online learning [19][20][21][22][23][24][25] that perceived usefulness of e-learning product has significant role in influencing the willingness of users to continue using the product. Besides having a good technical support and well designed, the online platform for learning as well as training must perceived as useful by the participants in motivating them to continue using it or other platforms like it.…”
Section: Discussionsupporting
confidence: 67%
“…Many of the results of previous e-learning studies such as on cloud e-learning application [19], Massive Open Online Course (MOOC) [20], Mobile web 2.0 [21], multimedia online learning [22], etc. suggested that learners' willingness to continue using the online learning platform depends on how they feel and enjoy the program [19][20].…”
Section: E-npqel In Leadership Preparatory Training Programmentioning
confidence: 99%
“…Thus, confirmation is positively correlated with satisfaction [37]. In the field of education, many studies have also used the ECT framework to explore student continuance intention [21,38,39]. Recent research using ECT to study online learning is summarized in Table 1.…”
Section: Expectation Confirmation Theorymentioning
confidence: 99%
“…If an IS outperforms expectations, users generate positive emotional responses to it, which in turn positively affects perceived performance and user satisfaction. A large number of studies on IS continuation have shown that it is feasible to apply the ECM to study users' continuance intention to use a product [44,79]. Akram et al [44] investigated the determinants of users' continuance intention to use mobile banking services using an extended ECM, and concluded that the confirmation following the first use of the mobile banking services had a significant impact on perceived performance and user satisfaction.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%